THE IMPROVEMENT OF PUBLIC PROCUREMENT MANAGEMENT AT GOVERNMENT AGENCIES OF MOSCOW - S. Zudenkova; E. Fokin (Вестник университета)
The arguments proving the need for the improvement of public procurement management at government agencies of Moscow are presented. The practice of the Federal Law № 44 published 5 April 2013, provisions application related to setting up of a contract service in sphere of public procurement is considered by the example of the authority of the South-Eastern administrative district of Moscow.